Cultural Adaptations in Clinical InteractiONs (CoACtION): a multi-site comparative study to assess what cultural adaptations are made by clinicians in different settings. (17th February 2021) - Rathod, Shanaya; Graves, Elizabeth; Kingdon, David; Thorne, Kerensa; Naeem, Farooq; Phiri, Peter
Abstract: Culture influences models of mental illness, help-seeking behaviours and outcomes of interventions. Cultural competency training has been developed to improve clinician practice in addressing these issues. The study aims to identify to what extent culturally competent and informed interactions are used by clinicians in England and how patients experience these interaction. Clinicians and non-white western patients were recruited to complete a questionnaire on culturally adapted practice in 25 areas of England. Clinicians are much more likely to rate their practice as clinically competent whereas patients were more likely to disagree that services were completely culturally competent. Length of time working as clinicians, receipt of specific cultural competence training and a higher percentage of caseload from non-white western backgrounds all increased clinician's perception that their practice was culturally competent. Clinicians recognised the importance of cultural competency but the disparity between their assessment of whether they achieved this and that of patients must be addressed. Ethics approval was obtained via proportionate review from the London – Central Research Ethics Committee (REC Ref no: 17/LO/1962). Study registration : UK Clinical Research Network Portfolio: 36744